The Pristine survey – V. A bright star sample observed with SOPHIE. Issue 3 (17th May 2019) - Bonifacio, P; Caffau, E; Sestito, F; Lardo, C; Martin, N F; Starkenburg, E; Sbordone, L; François, P; Jablonka, P; Henden, A A; Salvadori, S; González Hernández, J I; et al.
Abstract: With the aim of probing the properties of the bright end of the Pristine survey and its effectiveness in selecting metal-poor stars, we selected a sample of bright candidate metal-poor stars combining Pristine CaHK photometry with APASS gi photometry, before the Gaia second data release became available. These stars were observed with the SOPHIE spectrograph at the 1.93 m telescope of Observatoire de Haute Provence and we used photometry and parallaxes from Gaia DR2 to derive their atmospheric parameters. Chemical abundances were determined from the spectra for 40 stars of the sample. Eight stars were confirmed to be very metal-poor ([Fe/H] < −2.0), as expected from the photometric estimate. No star was found with [Fe/H] < −3.0, although for nine stars the photometric estimate was below this value. Three multiple systems are identified from their multipeaked cross-correlation functions. Two metal-poor stars with [Fe/H] ≈ −1.0 have an age estimate of about 4 Gyr. Accretion from a satellite galaxy is a possible explanation for these 'young metal-poor stars', but they could also be field blue stragglers. Galactic orbits for our sample of stars allowed us to divide them into three classes that we label 'Halo', 'Thick', and 'Thin' and tentatively identify as halo, thick disc, and thin disc. We present a new method for deriving photometric metallicities, effective temperatures, and surface gravities by combining Gaia parallaxes, photometry, and Pristine CaHK photometry. Comparison with spectroscopic metallicities shows a very good agreement and suggests that we can further improve the efficiency of Pristine CaHK in selecting metal-poor stars.